Routine pretreatment with abciximab versus standard periprocedural therapy in mechanically ventilated cardiogenic shock patients undergoing primary percutaneous coronary intervention: Subanalysis of the PRAGUE-7 study - Rokyta, R; Pechman, V; Tousek, P; Pudil, R; Lhotska, J; Widimsky, P (Experimental and clinical cardiology, 2013)
BACKGROUND: The clinical outcome of patients with myocardial infarction (MI) complicated by cardiogenic shock (CS) who require mechanical ventilation (MV) is poor. OBJECTIVE: To analyze the impact of abciximab pretreatment in this high-risk population of MI patients. METHODS: The present study was a retrospective subanalysis of the multicentre randomized Routine Upfront Abciximab Versus Standard Peri-Procedural Therapy in Patients Undergoing Percutaneous Coronary Intervention for Cardiogenic Shock (PRAGUE-7) study, which included 80 MI patients in CS undergoing primary percutaneous coronary intervention (PCI). Patients were randomly assigned into group A (routine pretreatment with an abciximab bolus followed by a 1 h abciximab infusion) and group B (standard therapy). The subanalysis included 37 patients requiring MV. Seventeen patients were in group A and 20 were in group B. The primary end point (death/stroke/reinfarction/new severe renal failure) at 30 days, procedural success (thrombosis in myocardial infarction [TIMI] flow) and frequency of bleeding were assessed. The χ(2) and Student's t tests were used for statistical analysis; P<0.05 was considered to be statistically significant. RESULTS: The primary end point occurred in nine (53%) patients in group A and 12 (60%) patients in group B (P=0.66). TIMI flow after primary PCI was higher in group A (2.75 versus 2.31; P<0.05). Major bleeding occurred in 12% of patients in group A versus 10% of patients in group B (P=0.86). Minor or minimal bleeding was more common in group A (29%) compared with group B (5%; P<0.05). CONCLUSION: The results of the present study suggest that routine pretreatment with abciximab before primary PCI in mechanically ventilated patients with MI complicated by cardiogenic shock was associated with better angiographic results but also with a higher incidence of bleeding.
Keywords: Acute coronary syndrome; Percutaneous coronary intervention; Mechanical ventilation; Abciximab; Cardiogenic shock; Intensive care